2011
DOI: 10.1519/jsc.0b013e3181fb4947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regular Heel-Raise Training Aimed at the Soleus Muscle on Dynamic Balance Associated With Arm Movement in Elderly Women

Abstract: The effects of low-intensity muscle training with heel-raises on dynamic balance associated with bilateral arm flexion were investigated in postmenopausal elderly women. Twenty-six elderly women were evenly grouped into training and control groups. Training group subjects performed 100 heel raises per day for 2 months. The training was aimed at hypertrophy of the soleus muscle, which has a relatively high proportion (ca. 90%) of slow-twitch muscle fibers and is one of the main postural muscles. Dynamic balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
12
1
1
Order By: Relevance
“…Our results are in contrast to those of Fujiwara et al. (2011), who reported a greater increase in MT of the soleus compared to the gastrocnemius (12.7% vs. 6.6%) following performance of one daily set of very low load standing plantarflexion exercise (100 repetitions) in a cohort of older women across a 2‐month study period. Discrepancies between the studies may be attributable to several factors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are in contrast to those of Fujiwara et al. (2011), who reported a greater increase in MT of the soleus compared to the gastrocnemius (12.7% vs. 6.6%) following performance of one daily set of very low load standing plantarflexion exercise (100 repetitions) in a cohort of older women across a 2‐month study period. Discrepancies between the studies may be attributable to several factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, Fujiwara et al. (2011) employed a very high repetition range using only bodyweight as resistance whereas the repetition range in our study, although generally considered high by RT standards, equated to ~¼ the number of repetitions performed in the former protocol. Differences in the populations studied (older women vs. younger men) may also have been a factor, as the aging process results in a gradual loss of fast‐twitch fibers whereby whole muscle develops a slower phenotype with an impaired capacity to generate force (Waters, Baumgartner, Garry, & Vellas, 2010).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, training of the ankle muscles using low to moderate intensities have been described as improving not only strength, but also dynamic responses. 37 Therefore, the waterbased program may be viewed as an interesting stimulus for modifying the postural responses by increasing the readiness of the system, i.e., the ability to react promptly to a perturbation. It may be also argued that the dynamic nature of the water-based training program may have influenced the ability to recover balance, but may have no effect on the ability to sustain a quiet static posture over time.…”
Section: Discussionmentioning
confidence: 99%
“…Fujiwara and colleagues 18 showed that heel-raising exercises in elderly women significantly increased gastrocnemius (6%) and soleus (12%) thickness, and McNee 21 showed that strength training in children with cerebral palsy increased the volume of the medial and lateral gastrocnemius muscles by about 15%. As such, it is clear that exercise training, in healthy young and old controls and diseased individuals, leads to increased muscle thickness and improves measures of strength and function.…”
Section: Muscle Ultrasonographymentioning
confidence: 99%